The Inconsistent Relationship between Education Quality Measurement System Scores and Grade Point Averages of 8th Grade Students in Chile - Vergara Díaz, Gaston (2019)
The Educational Quality Measurement System [SIMCE] has the institutional objective of improving the quality of education and keeping citizens abreast of the different types of learning achievements of the student body in Chile. However, not much tangible research has been done in this regard. The main purpose of this study is to establish a correlation between end of the year grades for 8th grade students and SICME scores attained by the students in Language and Communication, Mathematics and Natural Sciences tests. The data was collected from 8th grade students by the Quality Education Agency which pertains to Chile´s Ministry of Education. The original information included 12,586 students from the Southern Area of the country since it comprises the census of the five most important cities in Southern Chile which include Temuco, Valdivia, Osorno, Puerto Montt and Ancud which represents an extreme scenario. In order to complete this correlational analysis and unmask the results which had only took census data into account, a targeted sample was developed using the city of Temuco, the largest city, Ancud, the smallest and most remote city and a high school selected randomly among the five cities. It was determined that there is a weak relationship between SIMCE test scores and student grade point averages which proves that the national instrument used to gauge student learning in Chile´s Basic Education Cycle, differs significantly from those used by school faculty.